Reducing Unemployment Through Enhancement Entrepreneurship Education, Entrepreneurial Orientation and Entrepreneurial Intention - Suwarno, Henky Lisan; Malinda, Maya; Margaretha, Yolla; Aliwinoto, Christine (Universitas Bangka Belitung, 2023)
The unemployment rates in Indonesia are deemed to be elevated, and a potential strategy to tackle this predicament involves augmenting entrepreneurial intention among university students. This approach fosters job creation prospects after graduation rather than pursuing traditional employment options. Hence, this study aimed to analyze the impact of entrepreneurship education and orientation in enhancing intention of entrepreneurship among students at a Private University. To achieve this objective, a comprehensive data collection process was conducted, involving the distribution of questionnaires to 327 students who had previously received entrepreneurship education. The data analysis method employed was Structural Equation Modeling, enabling a rigorous examination of the relationships between the variables. The results showed a significant role played by education and orientation of entrepreneurship in enhancing intention of entrepreneurship among the students. Furthermore, these results offered valuable insights into the importance of three variables and elucidated their intricate interrelationships.